Do what you are : discover the perfect career for you through the secrets of personality type - Tieger, Paul D.; Barron-Tieger, Barbara; Tieger, Kelly (New York : Little, Brown and Company, 2014)
This book leads you step-by-step through the process of determining and verifying your personality type, providing real-life case studies of people who share your type and introducing you to the key ingredients your work must have for it to be genuinely fulfilling. Using workbook exercises and explaining specific job search strategies, Do What You Are identifies occupations that are popular with your type and offers a rundown of your work related strengths and weaknesses to customize your job search, ensuring the best results in the shortest time. Whether you are a millennial, a first-time job seeker, a baby boomer looking for a second act, or an established professional seeking post-career fulfillment, Do What You Are will help you discover the right career for you.
pt. 1. Unlocking the secrets of personality type -- Suit yourself : the secret of career satisfaction -- Just who do you think you are? Discovering your personality type -- Mirror, mirror : verifying your personality type -- pt. 2. The "fourmula" for career satisfaction -- What a character! The four different temperaments -- Who's on first? Identifying your innate strengths -- The way you do the things you do : which strengths you share and which you use privately -- Aged to perfection : developing your abilities over time -- pt. 3. Getting to work -- ENFJ : "the public relations specialists" -- INFJ : "catalysts for positive change" -- ENFP : "anything's possible" -- INFP : "still waters run deep" -- ENTJ : "everything's fine -- I'm in charge" -- INTJ : "competence + independence = perfection" -- ENTP : "life's entrepreneurs" -- INTP : "ingenious problem solvers" -- ESTJ : "taking care of business" -- ISTJ : "take your time and do it right" -- ESFJ : "what can I do for you?" -- ISFJ : "on my honor, to do my duty ..." -- ESTP : "let's get busy!" -- ISTP : "doing the best I can with what I've got" -- ESFP : "don't worry, be happy!" -- ISFP : "it's the thought that counts" -- Putting it all together : creating your personal career plan -- Enncore! Encore! : success stories of baby boomers finding satisfying second careers -- For career professionals only.
Includes bibliographical references and index.
Keywords: Personality and occupation; Myers-Briggs Type Indicator; Vocational guidance